NILAI KEPEMIMPINAN DALAM SALAT BERJAMAAH (TinjauanPendidikan Islam) - Imran, Ali; HM, M. Amir (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This paper discusses the values of leadership in congregational prayers according to a review of Islamic education. Aims to reveal the meaning of congregational prayer and describe the values of leadership in the implementation of congregational prayer from the perspective of Islamic education. This research is included in the type of library research. The data collection method is carried out by conducting searches through relevant journal articles and books. The results of the study indicate that congregational prayer is a prayer that is performed in a congregational manner, which is jointly led by a faith. In congregational prayers there are two shields that the leader in front is called the imam, while the second shield is those who follow him called the makmum. Of course, what is being done is a worship activity that is carried out in two parts, namely faith and belief and both doing what is called congregational prayer.Among the leadership values that are reflected in congregational prayers include: The leader is always in front, the leader has a qualified capacity, and also motivates his congregation to always do good and spread many benefits to others.